Improving Motivation in Translator Training: Achievement Goal Orientations of Translation Studies Students - Ayşe Işık Akdağ (Selçuk Üniversitesi Edebiyat Fakültesi Dergisi)
In order to improve the student motivation, this study aims to determine the opinions of Translation Studies students about achievement goal orientations in terms of variables such as gender, department, class and perception of academic achievement. Research is based on the relational screening model and the research data was collected by using the Goal Orientations Scale adapted to Turkish by Akın & Çetin (2007). During the academic year 2017-2018, 242 students studying in the German, French and English Translation Studies Departments at a state university participated in the research. As a result, it was observed that learning orientation, one of the three sub-dimensions of achievement goal orientations, varies significantly by gender and perception of academic achievement; and performance-approach orientation, other sub-dimension, by department and gender. No statistically significant relationship was found between variables and performance-avoidance orientation, the third sub-dimension.